2009
DOI: 10.1073/pnas.0901377106
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing web evolution and spider diversification in the molecular era

Abstract: The evolutionary diversification of spiders is attributed to spectacular innovations in silk. Spiders are unique in synthesizing many different kinds of silk, and using silk for a variety of ecological functions throughout their lives, particularly to make preycatching webs. Here, we construct a broad higher-level phylogeny of spiders combining molecular data with traditional morphological and behavioral characters. We use this phylogeny to test the hypothesis that the spider orb web evolved only once. We then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

18
384
2
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 348 publications
(406 citation statements)
references
References 64 publications
18
384
2
2
Order By: Relevance
“…More than 380 million years of evolution have produced >46,000 extant spider species, exhibiting an incredible diversity of silks used for prey capture and reproduction [1][2][3] . Spider silks can be stronger than steel and tougher than Kevlar, yet are much lighter weight than these manmade materials 4 .…”
mentioning
confidence: 99%
“…More than 380 million years of evolution have produced >46,000 extant spider species, exhibiting an incredible diversity of silks used for prey capture and reproduction [1][2][3] . Spider silks can be stronger than steel and tougher than Kevlar, yet are much lighter weight than these manmade materials 4 .…”
mentioning
confidence: 99%
“…Silk has played a key role in the radiation of spiders (Blackledge et al, 2009;Vollrath and Selden, 2007) following the colonisation of land by their ancestors in the early Devonian (Selden et al, 1991;Shear et al, 1989). The number of silk-producing glands and silk types that individual spiders produce has increased during the evolution of the group, and orb-weaving spiders spin seven different kinds of silk, including five fibrous silks that contain unique sets of proteins (Foelix, 1996).…”
mentioning
confidence: 99%
“…Most recent phylogenetic analyses of morphological and behavioral traits (Griswold et al 1998;Kuntner et al 2008), as well as molecular traits (Garb et al 2006;Blackledge et al 2009;Dimitrov et al 2012) have supported the single origin hypothesis for orb webs. The degree of support has been controversial, however (Dimitrov et al 2012), and the question of how ecribellate sticky lines evolved and replaced cribellate sticky lines without any known intermediate orb web forms that lacked sticky lines is still a puzzle (Opell & Schwend 2009).…”
mentioning
confidence: 97%
“…Until last year, a general consensus that favored the single origin hypothesis for orb webs seemed to be emerging, based on morphological and behavioral (Griswold et al 1998;Kuntner et al 2008) as well as molecular traits (Garb et al 2006;Blackledge et al 2009;Dimitrov et al 2012). In 2014, however, a pair of molecular analyses, which attempted to correct for several potential problems, including artificial inflation of support due to missing data, unequal rates of evolution in different lineages, compositional heterogeneity, and heterotachy (Fernandez et al 2014, Bond et al 2014, found support for linking the deinopoids more closely with a large group of about 40 non-orb weaving (and largely webless) families (the "RTA clade"), rather than with araneoids.…”
mentioning
confidence: 99%